Olaparib monotherapy or combination therapy in lung cancer: an updated systematic review and meta- analysis - Hajihosseini, Sajjad; Emami, Ehsan; Zakavi, Seyed Amirali; Jochin, Parnia; Shahrokhi, Mehregan; Khoshravesh, Sahar; Goli, Mitra; Belbasi, Mohaddeseh; Erabi, Gisou; Deravi, Niloofar (Frontiers in Oncology, 2025)
Background and aimsImpaired double strand DNA repair by homologous repair deficiency (HRD) leads to sensitivity to poly ADP ribose polymerase (PARP) inhibition. A subset of non-small cell lung cancers (NSCLCs) harbour impaired DNA double strand break repair. This study aims to investigate meta-analysis on the olaparib monotherapy or combination therapy in lung cancer.MethodsA comprehensive search was conducted in Pubmed, Scopus and Google Scholar data bases up to August 13, 2023 related articles were extracted title, abstract and full text of articles were screened. The quality included articles were assessing the data was extracted and hence analysis.ResultsAfter screening 5208 articles, 9 were selected for final review based on relevance to the topic. Olaparib monotherapy increased progression free survival (PFS) level [ES= 7.76; 95% CI= 0.16 to 1.36; P=0.208]. Olaparib maintenance therapy increased PFS compared to placebo in platinum-sensitive NSCLC patients [ES= 0.9; 95% CI= 0.9 to 0.9]. Combination therapy with durvalumab and olaparib decreased PFS level compared to the olaparib group [ES=6.07; 95% confidence interval (95% CI) = 0.67 to 11.46; P=0.000]. Adding gefitinib to olaparib decreased PFS compared to olaparib only group, significantly (ES=3.39; 95% CI=-0.78 to 7.56; P=0.609).ConclusionsOur study demonstrated olaparib as monotherapy can increase the PFS of patients with lung cancer, but the combination of olaparib and gefitinib or the combination of olaparib plus durvalumab couldn’t have a significant effect. According to the high heterogeneous rate of studies further large-scale randomized control trials are still required to progress association.Systematic Review RegistrationOpen Science Framework (OSF).